Нақл ва масал муносабати (SCIENCE and SOCIETY, 2019)
The article is devoted to the investigation of one of the actual issues in Uzbek and Karakalpak folklore- the study of genres of parable and fable. The author also studies the history of publication of works written in genres of parable and fable.